2003
DOI: 10.1097/01.aud.0000051689.57380.1b
|View full text |Cite
|
Sign up to set email alerts
|

Language Skills of Children with Early Cochlear Implantation

Abstract: Use of a cochlear implant has had a dramatic impact on the linguistic competence of profoundly hearing-impaired children. More than half of the children in this sample with average learning ability produced and understood English language at a level comparable with that of their hearing age mates. Such mature language outcomes were not typical of children with profound hearing loss who used hearing aids. Use of a visual (i.e., sign) language system did not provide the linguistic advantage that had been anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
302
9
31

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 476 publications
(372 citation statements)
references
References 21 publications
30
302
9
31
Order By: Relevance
“…In a study involving 134 children with cochlear implants, up to the age of 3, in which language development was assessed, those authors found that the best results were associated to the female gender. This was also corroborated by Geers et al (2007) 15 16 when they assessed 181 children from 8 to 9 years of age with cochlear implants. In effect, despite having no significant differences recorded, the doubt is maintained as to a possible influence of gender on linguistic gains of children with cochlear implant.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…In a study involving 134 children with cochlear implants, up to the age of 3, in which language development was assessed, those authors found that the best results were associated to the female gender. This was also corroborated by Geers et al (2007) 15 16 when they assessed 181 children from 8 to 9 years of age with cochlear implants. In effect, despite having no significant differences recorded, the doubt is maintained as to a possible influence of gender on linguistic gains of children with cochlear implant.…”
Section: Resultsmentioning
confidence: 50%
“…Although implanted children are capable of developing good linguistic capacities, the great variability of results between genders, observed by different authors, remains a matter of motivation 9,[14][15][16] . It is a fact that the number of individuals in our sample was relatively small.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carla Aparecida de Urzedo Fortunato Queiroz (1) , Maria Cecília Bevilacqua (2) , Maria da Piedade Resende da Costa (3) RESUMO Objetivo: analisar a compreensão verbal de crianças surdas usuárias de implante coclear (IC) por meio de um estudo longitudinal. Métodos: os participantes foram nove crianças surdas usuárias de IC.…”
Section: Longitudinal Study Of Verbal Comprehension Of Children With unclassified
“…A idade cronológica das crianças variou entre quatro e oito anos e o tempo de uso do IC foi, em média, 1 ano e 6 meses na 1ª avaliação, 3 anos e 7 meses na 2ª avaliação e 4 anos e 9 meses na 3ª avaliação. [2][3][4][5] . Ele fornece, especi camente, acesso a informações em frequências altas, o que em geral não é observado com o uso de aparelho auditivo 6 .…”
Section: Longitudinal Study Of Verbal Comprehension Of Children With unclassified